Efficacy of bioceramic and calcium hydroxide-based root canal sealers against pathogenic endodontic biofilms: An In vitro study - Tien Suwartini; Jessica Santoso; Armelia Sari Widyarman; Dina Ratnasari (Wolters Kluwer Medknow Publications, 2022)
Background: Complete eradication of root canal pathogens cannot be predictably achieved by chemomechanical preparation and root canal disinfection. Therefore, an obturation material that has superior antimicrobial activity and sealing ability is required to inactivate residual microbes and prevent them from reentering the root canal system. Recently developed bioceramic root canal sealers are hydraulic cement which form calcium hydroxide during the hydration process. Like calcium hydroxide sealers, they exert an antimicrobial effect by releasing hydroxyl ions and increasing the pH. Objective: The objective of this study was to evaluate and compare the antimicrobial activity of a calcium hydroxide-based sealer and two bioceramic sealers against Porphyromonas gingivalis, Enterococcus faecalis, and Candida albicans biofilms. Materials and Methods: The sealers were dissolved in sterile saline to obtain supernatants. Biofilm formation assays, colony counting, and real-time polymerase chain reaction (PCR) were performed to evaluate the antimicrobial activity of each supernatant. The data were analyzed using one-way analysis of variance. Results: All sealers exerted effects against all three microbial biofilms. The biofilm formation assays showed that the bioceramic sealers were more effective against P. gingivalis and E. faecalis biofilms. In contrast, colony counting and real-time PCR showed that the calcium hydroxide sealer was significantly more effective than the bioceramic sealers. All tests showed that the calcium hydroxide sealer was more effective against C. albicans, with the colony count and real-time PCR results showing statistically significant differences. Conclusion: The calcium hydroxide-based sealer was more effective than the bioceramic sealers in eradicating pathogenic root canal biofilms.